An Exploratory Factor Analysis of Brand Awareness in The Low Involvement Product on Social Media Channel - Jitprapai, Nutthapon; Kittisaereekul, Sidunuch; Limsumlitnipa, Thitiphat (Future Science / FSH-PH Publications, 2021)
The objective of this paper was to analyse the factor of brand awareness in the low involvement product on social media channel. Samples of this research were 500 people have experience with product on social media channel. The research instrument was a questionnaire. The statistics used for data analysis were frequency, percentage, average, standard deviation and the KMO and Bartlett’s test to measure the adequacy of the data and hypothesis test. The study results indicate that brand awareness in the low involvement product on social media channel which a total of four factors were extracted from the brand awareness index scale: product quality, presenter image, message design, and media characteristic. the KMO value is 0.95, Chi-square is 12418.36, p-value is 0.00 conclude that the variables were related and suitable with factor analyzing.